Social Issues in Supply Chain Sustainability – Focus Areas for Energy and Manufacturing sectors in India and USA - Nair, Prashant Unnikrishnan; Thankamony, Parvathy (European Journal of Sustainable Development, 2021)
The paper is a capsule to understand various social issues in supply chain, the social sustainability practices and strategies used for mitigation. Data was collected through questionnaire survey and systematic literature review of the supply chain social sustainability papers, published in peer-reviewed journals within the time frame of January 2000 to October 2020. Findings from this study show that social aspects are less researched and practiced compared to economic and environmental dimensions of sustainability. Research is still at an infancy stage in the emerging economies with very few social sustainability-centered studies focusing on practices and metrics to measure the impact of these practices. The paper identifies 26 social issues for social sustainability in supply chain for two different economies and does a comparative study. Scope of the paper is limited to Manufacturing and Energy sectors in the USA and in India to seek a possible contrasting or adhering perspective to the issues. Results and discussion pertain to the chosen sectors and geographies and provide key insight on the perspectives in the region with a conclusion on further research and mitigation methods through research and implementation of corporate practices that can help mitigate systemic social issues.